Cobalt and strontium based catalyst for conversion of hydrocarbons to syngas
By introducing composite oxides with a specific Co:Sr weight ratio in the catalyst formulation, the problem of difficulty in activation of Co-containing catalysts in the prior art is solved, and efficient activation of the catalyst and cost efficiency are achieved.
Patent Information
- Application Number
- CN202380051267.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-01
- Filing Date
- 2023-06-30
- Publication Date
- 2025-02-18
AI Technical Summary
There are difficulties in the activation process of existing Co-containing catalysts, resulting in increased production costs and it is difficult to improve the activation speed and cost efficiency of the catalyst.
Using lanthanum-containing composite oxide catalyst formulations, the reduction properties of the catalyst at low temperatures are significantly improved by specific Co:Sr weight ratio (0.01:1 to 20:1) and phase composition (such as Sr12O19, CoAl2O4, LaAlO3, etc.). and activation speed.
The efficient activation of the catalyst is achieved, the production cost is reduced, and the cost efficiency of the catalyst is significantly improved, so that it can reach a high activation state in a short time.
Smart Images

Figure BDA0005221542510000211 
Figure BDA0005221542510000221 
Figure BDA0005221542510000231
Abstract
Description
Technical Field
[0001] The present invention relates to a composite oxide comprising oxygen, lanthanum, aluminum, strontium and cobalt, wherein the composite oxide has a specific Co:Sr weight ratio. In addition, the present invention relates to a method for producing the composite oxide and a composite oxide obtainable or obtained by said method. Still further, the present invention relates to a method for producing a catalyst for converting hydrocarbons into synthesis gas, and a catalyst obtainable or obtained by said method. Still further, the present invention relates to a method for converting hydrocarbons into synthesis gas. DETAILED DESCRIPTION
[0002] Catalysts based on oxides containing Ni or Co are commonly used to reform hydrocarbons into synthesis gas. The use of Co-containing catalysts reduces production costs because they allow lower steam content in the feed. However, difficulties in activating Co-containing catalysts lead to increased production costs because special activation procedures are usually required.
[0003] WO 2013 / 118078 A1 relates to a Ni or Co-containing hexaaluminate catalyst for reforming hydrocarbons. WO2014 / 135642 A1 relates to a Ni-containing hexaaluminate catalyst for reforming hydrocarbons in the presence of CO2. Similarly, WO2015 / 091310 A1 relates to a method for reforming a mixture of hydrocarbons and CO2. US2016 / 0207031 A1 and US9566571 B2 specifically relate to a method for producing a catalyst for reforming hydrocarbons from a feed gas containing methane and CO2.
[0004] On the other hand, WO 2014 / 001423 A1 relates to a high-pressure process for the reforming of hydrocarbons with CO2 in the presence of an Ir-containing catalyst. WO 2015 / 135968 A1, for its part, relates to yttrium-containing catalysts for high-temperature CO2 hydration and / or reforming.
[0005] WO 2016 / 062853 A1 relates to the synthesis of aluminates by flame spray pyrolysis.
[0006] Finally, WO 2020 / 157202 A1 relates to a molding comprising a mixed oxide of lanthanum, aluminum and cobalt.
[0007] Although many modifications have been made in the past, there remains a need for improved catalyst formulations, particularly with regard to their cost effectiveness, and more particularly with regard to the activation of Co-containing catalysts for the reforming of hydrocarbons to synthesis gas. DETAILED DESCRIPTION
[0009] It is therefore an object of the present invention to provide a Co-containing catalyst formulation, and in particular a Co-containing catalyst formulation for converting hydrocarbons into synthesis gas in the presence of steam and / or CO2, wherein the catalyst formulation allows a gentler activation of the Co-containing catalyst, and in particular wherein the speed of catalyst activation is increased. Thus, it has been unexpectedly found that a Co-containing catalyst formulation containing lanthanum, wherein Sr is further included in a Co:Sr weight ratio within a specific range, allows a significantly higher reducibility of the catalyst at low temperatures, as a result of which the activation of the catalyst is significantly improved and can therefore be achieved in a much shorter period of time. As a result, it has been quite unexpectedly found that a highly cost-effective Co-containing catalyst can be provided.
[0010] Therefore, the present invention relates to a composite oxide comprising oxygen, lanthanum, aluminum, strontium and cobalt, wherein the Co:Sr weight ratio of cobalt to strontium in the composite oxide is in the range of 0.01:1 to 20:1, preferably 0.03:1 to 10:1, more preferably 0.05:1 to 5:1, more preferably 0.08:1 to 2:1, more preferably 0.10:1 to 1.50:1, more preferably 0.15:1 to 1.25:1, more preferably 0.20:1 to 1.10:1, more preferably 0.25:1 to 0.95:1, more preferably 0.30:1 to 0.80:1, more preferably 0.35:1 to 0.65:1, more preferably 0.40:1 to 0.55:1, and more preferably 0.43:1 to 0.47:1, calculated as the element.
[0011] Preferably, the composite oxide contains 1 to 15 wt.-%, more preferably 2.5 to 12.0 wt.-%, more preferably 4.0 to 10.5 wt.-%, more preferably 5.5 to 9.0 wt.-%, more preferably 6.1 to 8.4 wt.-%, more preferably 6.3 to 8.2 wt.-%, more preferably 6.5 to 8.0 wt.-%, more preferably 6.7 to 7.8 wt.-%, more preferably 6.8 to 7.7 wt.-% cobalt, calculated as the element.
[0012] Preferably, the composite oxide contains 1 to 22.0 wt.-%, more preferably 2.5 to 20.0 wt.-%, more preferably 4.0 to 18.5 wt.-%, more preferably 5.0 to 17.5 wt.-%, more preferably 5.3 to 17.2 wt.-%, more preferably 5.6 to 16.9 wt.-%, more preferably 5.8 to 16.7 wt.-%, more preferably 5.9 to 16.6 wt.-%, more preferably 6.0 to 16.5 wt.-% strontium, calculated as the element.
[0013] Preferably, the composite oxide contains 3.0 to 20.0 wt.-%, more preferably 5.0 to 18.0 wt.-%, more preferably 6.0 to 17.0 wt.-%, more preferably 6.8 to 16.2 wt.-%, more preferably 7.1 to 15.9 wt.-%, more preferably 7.4 to 15.6 wt.-%, more preferably 7.6 to 15.4 wt.-%, more preferably 7.7 to 15.3 wt.-%, more preferably 7.8 to 15.2 wt.-% lanthanum, calculated as the element.
[0014] Preferably, the composite oxide contains 26.0 to 45 wt.-%, more preferably 27.8 to 43.1 wt.-%, more preferably 28.8 to 42.1 wt.-%, more preferably 29.8 to 41.1 wt.-%, more preferably 30.3 to 40.6 wt.-%, more preferably 30.8 to 40.1 wt.-%, more preferably 31.1 to 39.8 wt.-%, more preferably 31.3 to 39.6 wt.-%, more preferably 31.4 to 39.5 wt.-% aluminum, calculated as the element.
[0015] Preferably, the Co:Al weight ratio of cobalt to aluminum in the composite oxide is in the range of 0.02:1 to 0.50:1, more preferably 0.05:1 to 0.45:1, more preferably 0.08:1 to 0.38:1, more preferably 0.10:1 to 0.33:1, more preferably 0.12:1 to 0.30:1, more preferably 0.14:1 to 0.27:1, more preferably 0.16:1 to 0.25:1, more preferably 0.18:1 to 0.23:1, more preferably 0.19:1 to 0.22:1, calculated as the element.
[0016] Preferably, the Sr:La weight ratio of strontium to lanthanum in the composite oxide is in the range of 0.10:1 to 2.70:1, more preferably 0.20:1 to 2.50:1, more preferably 0.30:1 to 2.40:1, more preferably 0.40:1 to 2.30:1, more preferably 0.50:1 to 2.20:1, more preferably 0.60:1 to 2.10:1, more preferably 0.64:1 to 2.06:1, more preferably 0.66:1 to 2.04:1, more preferably 0.67:1 to 2.03:1, calculated as the element.
[0017] Preferably, the composite oxide comprises SrAl 12 O 19 Mutually.
[0018] Wherein the composite oxide comprises SrAl 12 O 19 In the case of a phase, it is preferred that the composite oxide contains the SrAl 12 O 19phase, the amount of which ranges from 10 to 80 wt.-%, more preferably from 15 to 70 wt.-%, more preferably from 20 to 60 wt.-%, 25 to 55 wt.-%, more preferably from 30 to 53 wt.-%, more preferably from 35 to 51 wt.-%, more preferably from 37 to 49 wt.-%, more preferably from 39 to 47 wt.-%, and more preferably from 41 to 45 wt.-%, based on 100 wt.-% of the composite oxide.
[0019] In the composite oxide, SrAl 12 O 19 The amount of the phase is preferably determined according to the method of Reference Example 1.
[0020] Preferably, the composite oxide contains a Sr(Al2O4) phase.
[0021] In the case where the composite oxide contains a Sr(Al2O4) phase, it is preferred that the composite oxide contains the Sr(Al2O4) phase in an amount ranging from 0.5 to 50 wt.-%, more preferably from 1 to 40 wt.-%, more preferably from 2 to 30 wt.-%, more preferably from 3 to 25 wt.-%, 3 to 25 wt.-%, more preferably from 4 to 20 wt.-%, more preferably from 5 to 18 wt.-%, more preferably from 6 to 15 wt.-%, more preferably from 7 to 12 wt.-%, and more preferably from 8 to 10 wt.-%, based on 100 wt.-% of the composite oxide.
[0022] Wherein the amount of the Sr(Al2O4) phase in the composite oxide is preferably determined according to the method of Reference Example 1.
[0023] Preferably, the composite oxide contains a LaSrAl3O7 phase.
[0024] In the case where the composite oxide contains a LaSrAl3O7 phase, it is preferred that the composite oxide contains the LaSrAl3O7 phase in an amount ranging from 0 to 6 wt.-%, more preferably from 0.1 to 4 wt.-%, more preferably from 0.2 to 3 wt.-%, more preferably from 0.4 to 2.5 wt.-%, more preferably from 0.6 to 2 wt.-%, 0.6 to 2 wt.-%, more preferably from 0.8 to 1.8 wt.-%, more preferably from 1.0 to 1.6 wt.-%, and more preferably from 1.2 to 1.4 wt.-%, based on 100 wt.-% of the composite oxide.
[0025] The amount of the LaSrAl3O7 phase in the composite oxide is preferably determined according to the method of Reference Example 1.
[0026] Preferably, the composite oxide contains a LaAlO 3 phase.
[0027] In the case where the composite oxide contains a LaAlO3 phase, it is preferred that the composite oxide contains the LaAlO3 phase in an amount ranging from 1 to 35 wt.-%, more preferably from 3 to 32 wt.-%, more preferably from 5 to 30 wt.-%, 10 to 28 wt.-%, more preferably from 12 to 25 wt.-%, more preferably from 13 to 23 wt.-%, more preferably from 15 to 20 wt.-%, and more preferably from 17 to 18 wt.-%, based on 100 wt.-% of the composite oxide.
[0028] The amount of the LaAlO3 phase in the composite oxide is preferably determined according to the method of Reference Example 1.
[0029] Preferably, the composite oxide comprises a CoAl2O4 phase, more preferably a CoAl2O4 spinel phase.
[0030] In the case where the composite oxide comprises a CoAl2O4 phase, preferably a CoAl2O4 spinel phase, it is further preferred that the composite oxide comprises the CoAl2O4 phase in an amount ranging from 15.4 to 40 wt.-%, more preferably from 16.4 to 32 wt.-%, more preferably from 17.4 to 28 wt.-%, more preferably from 17.9 to 26 wt.-%, more preferably from 19 to 24 wt.-%, more preferably from 19.5 to 23 wt.-%, more preferably from 20 to 22 wt.-%, based on 100 wt.-% of the composite oxide.
[0031] The amount of the CoAl2O4 phase in the composite oxide is preferably determined according to the method of Reference Example 1.
[0032] Preferably, the composite oxide contains a Sr2CoO4 phase.
[0033] In the case where the composite oxide contains a Sr2CoO4 phase, it is preferred that the composite oxide contains the Sr2CoO4 phase in an amount ranging from 1 to 20 wt.-%, more preferably from 3 to 16 wt.-%, from 4 to 14 wt.-%, more preferably from 5 to 12 wt.-%, more preferably from 6 to 10 wt.-%, and more preferably from 7 to 8 wt.-%, based on 100 wt.-% of the composite oxide.
[0034] Wherein the amount of the Sr2CoO4 phase in the composite oxide is preferably determined according to the method of Reference Example 1.
[0035] Preferably, the composite oxide contains 100 wt.-%, 1 wt.-% or less, more preferably 0.5 wt.-% or less, more preferably 0.1 wt.-% or less, more preferably 0.05 wt.-% or less, more preferably 0.01 wt.-% or less, more preferably 0.005 wt.-% or less, and more preferably 0.001 wt.-% or less of LaCoAl based on the composite oxide. 11 O 19 phase, wherein the composite oxide preferably does not contain LaCoAl 11 O 19 Mutually,
[0036] Among them, LaCoAl 11 O 19 The amount of the phase is preferably determined according to the method of Reference Example 1.
[0037] Preferably, the composite oxide shows a crystallinity ranging from 30% to 95%, more preferably from 38% to 87%, more preferably from 43% to 82%, more preferably from 46% to 79%, more preferably from 48% to 77%, more preferably from 49% to 76%,
[0038] The crystallinity of the composite oxide is preferably determined according to the method of Reference Example 1.
[0039] Preferably, 99 to 100 wt-%, more preferably 99.5 to 100 wt-%, more preferably 99.9 to 100 wt-% of the composite oxide consists of oxygen, lanthanum, aluminum, strontium, cobalt and optionally hydrogen.
[0040] The composite oxide is preferably in the form of a powder or a molded article, more preferably in the form of a molded article.
[0041] In the case where the composite oxide is in the form of a powder or a molding, preferably in the form of a molding, it is further preferred that 99 to 100 wt.-%, more preferably 99.5 to 100 wt.-%, more preferably 99.9 to 100 wt.-% of the powder or the molding consists of the composite oxide.
[0042] Preferably, the composite oxide is obtained or obtainable according to the method of any one of the specific and preferred embodiments of the present invention for producing a composite oxide.
[0043] The present invention also relates to a method for producing a composite oxide, preferably a composite oxide according to any one of the specific and preferred embodiments of the present invention, comprising
[0044] (i) preparing a mixture of one or more Al sources, one or more Co sources, one or more Sr sources and one or more La sources;
[0045] (ii) adding an acidic aqueous solution to the mixture prepared in (i);
[0046] (iii) homogenizing the mixture obtained in (ii);
[0047] (iv) optionally shaping the mixture obtained in (iii), preferably by extrusion, to obtain a shaped body;
[0048] (v) optionally drying the mixture obtained in (iii) or the shaped body obtained in (iv);
[0049] (vi) optionally pre-calcining the mixture obtained in (iii) or (v), or the shaped body obtained in (iv) or (v);
[0050] (vii) optionally grinding the dried and / or precalcined mixture or shaped body obtained in (v) or (vi);
[0051] (viii) optionally tableting the ground product obtained in (vii);
[0052] (ix) calcining the mixture obtained in (iii), (v), or (vi), or the shaped body obtained in (iv), (v), or (vi), or the ground product obtained in (vii), or the tableted product obtained in (viii).
[0053] In this regard, it is preferred that the one or more Al sources are selected from the group consisting of alumina trihydrate, Al2O3·0.5H2O, Al2O3, AlO(OH) (preferably boehmite), sodium aluminate, a mixture of two or more thereof, preferably selected from the group consisting of gibbsite (α-trihydrate alumina), behemothite (β-trihydrate alumina), nordstrandite (γ-trihydrate alumina), pseudo-amorphous alumina trihydrate, Al2O3·0.5H2O, Al2O3, AlO(OH) (preferably boehmite), sodium aluminate and a mixture of two or more thereof, wherein the one or more alumina sources are more preferably AlO(OH).
[0054] Preferably, the one or more Co sources are selected from the group consisting of cobalt carbonate, cobalt oxalate, cobalt acetate, cobalt tartrate, cobalt formate, cobalt sulfate, cobalt sulfide, cobalt fluoride, cobalt chloride, cobalt bromide, cobalt iodide and a mixture of two or more thereof, wherein the one or more Co sources are more preferably cobalt carbonate, more preferably cobalt carbonate, wherein the cobalt carbonate more preferably comprises, more preferably is CoCO3·yH2O, wherein 0≤y≤7, preferably 0≤y≤6.
[0055] Preferably, the one or more La sources are selected from the group consisting of lanthanum carbonate, lanthanum oxalate, lanthanum acetate, lanthanum tartrate, lanthanum formate, lanthanum sulfate, lanthanum sulfide, lanthanum fluoride, lanthanum chloride, lanthanum bromide, lanthanum iodide and a mixture of two or more thereof, wherein the one or more La sources are more preferably lanthanum carbonate, wherein the lanthanum carbonate more preferably comprises, more preferably is, La2(CO3)3·xH2O, wherein 0≤x≤10, more preferably 0≤x≤6.
[0056] Preferably, the one or more Sr sources are selected from the group consisting of strontium carbonate, strontium fluoride, strontium chloride, strontium bromide, strontium iodide, strontium sulfate, strontium nitrate, strontium hydroxide, strontium oxide and a mixture of two or more thereof, wherein the one or more Sr sources are more preferably strontium carbonate.
[0057] Preferably, the mixture in (i) is prepared by kneading the one or more sources of Al, Co, Sr and La.
[0058] Preferably, the acidic aqueous solution added in (ii) comprises one or more of formic acid, acetic acid, propionic acid, nitric acid, nitrous acid, citric acid, tartaric acid and oxalic acid, more preferably one or more of formic acid and nitric acid, wherein the acidic aqueous solution added in (ii) more preferably comprises formic acid.
[0059] Preferably, the homogenization in (iii) is achieved by stirring, more preferably kneading, the mixture obtained in (ii).
[0060] Preferably, the drying in (v) is performed at a temperature in the range of 80°C to 150°C, more preferably in the range of 95°C to 120°C, more preferably in the range of 100°C to 110°C.
[0061] Preferably, the drying in (v) is carried out for a duration in the range of 4 to 18 h, more preferably in the range of 6 to 12 h, more preferably in the range of 8 to 10 h.
[0062] Preferably, the pre-calcination in (vi) is carried out at a temperature in the range of 300°C to 600°C, more preferably in the range of 350°C to 500°C, more preferably in the range of 400°C to 450°C.
[0063] Preferably, the pre-calcination in (vi) is carried out for a duration in the range of 1 to 8 h, more preferably in the range of 3 to 5 h, more preferably in the range of 3.5 to 4.5 h.
[0064] Preferably, the calcination in (vi) is carried out at a temperature in the range of 800°C to 1500°C, more preferably in the range of 1000°C to 1400°C, more preferably in the range of 1100°C to 1300°C.
[0065] Preferably, the calcination in (vi) is carried out for a duration in the range of 1 to 8 h, more preferably in the range of 3 to 5 h, more preferably in the range of 3.5 to 4.5 h.
[0066] The present invention also relates to a composite oxide obtainable or obtained according to the method of any one of the specific and preferred embodiments of the present invention for producing a composite oxide.
[0067] The invention also relates to a method for producing a catalyst for converting hydrocarbons into synthesis gas, the method comprising
[0068] (1) providing a composite oxide according to any one of the specific and preferred embodiments of the present invention, or preparing a composite oxide by the method according to any one of the specific and preferred embodiments of the present invention for producing a composite oxide;
[0069] (2) Reducing the composite oxide prepared in (1) to obtain a catalyst.
[0070] Preferably, the reduction in (2) is carried out in an atmosphere comprising one or more reducing agents, wherein the one or more reducing agents comprise one or more of methane, hydrogen and carbon monoxide, more preferably methane and / or hydrogen, wherein methane is more preferably used as the reducing agent in (2).
[0071] The reduction in (2) is preferably performed at a temperature ranging from 500°C to 1,200°C, more preferably from 600°C to 1,100°C, more preferably from 700°C to 1,050°C, more preferably from 750°C to 1,000°C, more preferably from 800°C to 950°C, and more preferably from 850°C to 900°C.
[0072] Preferably, the reduction in (2) is carried out at a pressure in the range of 5 to 40 absolute bar, more preferably 10 to 35 absolute bar, more preferably 12 to 30 absolute bar, more preferably 14 to 25 absolute bar, more preferably 16 to 22 absolute bar, and more preferably 18 to 20 absolute bar.
[0073] Preferably, the reduction in (2) is carried out for a duration ranging from 0.5 to 24 h, more preferably from 1 to 18 h, more preferably from 3 to 10 h, and more preferably from 5 to 7 h.
[0074] The present invention also relates to a catalyst for converting hydrocarbons into synthesis gas, obtainable or obtained according to the method according to any one of the specific and preferred embodiments of the present invention for producing a catalyst for converting hydrocarbons into synthesis gas.
[0075] The present invention also relates to a method for converting hydrocarbons into synthesis gas, the method comprising
[0076] (A) providing a composite oxide according to any one of the specific and preferred embodiments of the present invention, or a catalyst for converting hydrocarbons into synthesis gas according to any one of the specific and preferred embodiments of the present invention;
[0077] (B) preparing a gas stream comprising one or more hydrocarbons and one or more of CO2 and H2O;
[0078] (C) contacting the gas stream prepared in (B) with the composite oxide or the catalyst provided in (A) at a temperature ranging from 700°C to 1,200°C, preferably 750°C to 1,100°C, more preferably 800°C to 1,050°C, more preferably 850°C to 1,000°C, and more preferably 900°C to 950°C.
[0079] Preferably, the gas stream produced in (B) comprises one or more hydrocarbons, CO2 and H2O.
[0080] Preferably, the one or more hydrocarbons are selected from the group consisting of C1-C10 alkanes, more preferably C1-C8 alkanes, more preferably C1-C6 alkanes, more preferably C1-C4 alkanes, more preferably C1-C3 alkanes, and more preferably C1-C2 alkanes, wherein more preferably the gas stream prepared in (B) comprises one or more of methane, ethane and propane, wherein more preferably the gas stream prepared in (B) comprises methane and / or ethane, preferably methane, wherein more preferably the one or more hydrocarbons contained in the gas stream prepared in (B) consist of methane and / or ethane, preferably methane.
[0081] Preferably the gas stream prepared in (B) comprises 20 to 80 vol.-%, more preferably 25 to 60 vol.-%, more preferably 30 to 50 vol.-%, more preferably 35 to 45 vol.-%, and more preferably 38 to 42 vol.-% of the one or more hydrocarbons.
[0082] Preferably, the gas stream prepared in (B) comprises 20 to 80 vol.-%, more preferably 25 to 60 vol.-%, more preferably 30 to 50 vol.-%, more preferably 35 to 45 vol.-%, and more preferably 38 to 42 vol.-% CO2.
[0083] Preferably, the gas stream prepared in (B) comprises 1 to 30 vol.-%, more preferably 5 to 25 vol.-%, more preferably 10 to 20 vol.-%, more preferably 12 to 18 vol.-%, and more preferably 14 to 16 vol.-% H2O.
[0084] Preferably, the gas stream prepared in (B) further comprises one or more inert gases, wherein these inert gases are more preferably selected from the group consisting of rare gases, nitrogen and mixtures of two or more thereof, wherein more preferably the gas stream further comprises nitrogen and / or argon, preferably nitrogen.
[0085] In the case where the gas stream prepared in (B) further comprises one or more inert gases, it is preferred that the gas stream prepared in (B) comprises 0 to 25 vol.-%, more preferably 0.5 to 15 vol.-%, more preferably 1 to 10 vol.-%, more preferably 3 to 8 vol.-%, and more preferably 4 to 6 vol.% of the one or more inert gases.
[0086] Preferably, the contacting in (C) is carried out at a pressure in the range of 5 to 40 absolute bar, more preferably 10 to 35 absolute bar, more preferably 12 to 30 absolute bar, more preferably 14 to 25 absolute bar, more preferably 16 to 22 absolute bar, and more preferably 18 to 20 absolute bar.
[0087] Preferably, the contacting in (C) is carried out for 500 to 25,000 hours. -1 , more preferably 1,000 to 15,000h -1 , more preferably 3,000 to 10,000h -1 , more preferably 4,000 to 8,000h -1 , and more preferably 5,000 to 7,000h -1 The gas hourly space velocity is within the range.
[0088] The present invention is further illustrated by the following group of examples and the combination of examples obtained by the dependencies and back references as shown. In particular, it should be noted that in each case where a series of examples is mentioned, for example in the context of terms such as "complex oxides as described in any one of Examples 1 to 4", each example in this series is intended to be disclosed clearly to the skilled person, that is, the wording of this term should be understood by the skilled person as synonymous with "complex oxides as described in any one of Examples 1, 2, 3 and 4". In addition, it is explicitly pointed out that the following group of examples is not a group of claims that determines the scope of protection, but represents an appropriate structural part of this specification related to the general and preferred aspects of the present invention.
[0089] 1. A composite oxide comprising oxygen, lanthanum, aluminum, strontium and cobalt, wherein the Co:Sr weight ratio of cobalt to strontium in the composite oxide is in the range of 0.01:1 to 20:1, preferably 0.03:1 to 10:1, more preferably 0.05:1 to 5:1, more preferably 0.08:1 to 2:1, more preferably 0.10:1 to 1.50:1, more preferably 0.15:1 to 1.25:1, more preferably 0.20:1 to 1.10:1, more preferably 0.25:1 to 0.95:1, more preferably 0.30:1 to 0.80:1, more preferably 0.35:1 to 0.65:1, more preferably 0.40:1 to 0.55:1, and more preferably 0.43:1 to 0.47:1, calculated as the element.
[0090] 2. A composite oxide as described in Example 1, wherein the composite oxide contains 1 to 15 wt.-%, preferably 2.5 to 12.0 wt.-%, more preferably 4.0 to 10.5 wt.-%, more preferably 5.5 to 9.0 wt.-%, more preferably 6.1 to 8.4 wt.-%, more preferably 6.3 to 8.2 wt.-%, more preferably 6.5 to 8.0 wt.-%, more preferably 6.7 to 7.8 wt.-%, more preferably 6.8 to 7.7 wt.-% cobalt, calculated as the element.
[0091] 3. A composite oxide as described in Example 1 or 2, wherein the composite oxide contains 1 to 22.0 wt.-%, preferably 2.5 to 20.0 wt.-%, more preferably 4.0 to 18.5 wt.-%, more preferably 5.0 to 17.5 wt.-%, more preferably 5.3 to 17.2 wt.-%, more preferably 5.6 to 16.9 wt.-%, more preferably 5.8 to 16.7 wt.-%, more preferably 5.9 to 16.6 wt.-%, more preferably 6.0 to 16.5 wt.-% strontium, calculated as the element.
[0092] 4. A composite oxide as described in any one of Examples 1 to 3, wherein the composite oxide contains 3.0 to 20.0 wt.-%, preferably 5.0 to 18.0 wt.-%, more preferably 6.0 to 17.0 wt.-%, more preferably 6.8 to 16.2 wt.-%, more preferably 7.1 to 15.9 wt.-%, more preferably 7.4 to 15.6 wt.-%, more preferably 7.6 to 15.4 wt.-%, more preferably 7.7 to 15.3 wt.-%, more preferably 7.8 to 15.2 wt.-% lanthanum, calculated as the element.
[0093] 5. A composite oxide as described in any one of Examples 1 to 4, wherein the composite oxide contains 26.0 to 45 wt.-%, preferably 27.8 to 43.1 wt.-%, more preferably 28.8 to 42.1 wt.-%, more preferably 29.8 to 41.1 wt.-%, more preferably 30.3 to 40.6 wt.-%, more preferably 30.8 to 40.1 wt.-%, more preferably 31.1 to 39.8 wt.-%, more preferably 31.3 to 39.6 wt.-%, more preferably 31.4 to 39.5 wt.-% aluminum, calculated as the element.
[0094] 6. A composite oxide as described in any one of Examples 1 to 5, wherein the Co:Al weight ratio of cobalt to aluminum in the composite oxide is in the range of 0.02:1 to 0.50:1, preferably 0.05:1 to 0.45:1, more preferably 0.08:1 to 0.38:1, more preferably 0.10:1 to 0.33:1, more preferably 0.12:1 to 0.30:1, more preferably 0.14:1 to 0.27:1, more preferably 0.16:1 to 0.25:1, more preferably 0.18:1 to 0.23:1, more preferably 0.19:1 to 0.22:1, calculated as element.
[0095] 7. A composite oxide as described in any one of Examples 1 to 6, wherein the weight ratio of strontium to lanthanum (Sr:La) in the composite oxide is in the range of 0.10:1 to 2.70:1, preferably 0.20:1 to 2.50:1, more preferably 0.30:1 to 2.40:1, more preferably 0.40:1 to 2.30:1, more preferably 0.50:1 to 2.20:1, more preferably 0.60:1 to 2.10:1, more preferably 0.64:1 to 2.06:1, more preferably 0.66:1 to 2.04:1, more preferably 0.67:1 to 2.03:1, calculated as element.
[0096] 8. The composite oxide as described in any one of embodiments 1 to 7, wherein the composite oxide comprises SrAl 12 O 19 Mutually.
[0097] 9. The composite oxide as described in Example 8, wherein the composite oxide comprises the SrAl 12 O 19 phase, the amount of which ranges from 10 to 80 wt.-%, preferably from 15 to 70 wt.-%, more preferably from 20 to 60 wt.-%, from 25 to 55 wt.-%, more preferably from 30 to 53 wt.-%, more preferably from 35 to 51 wt.-%, more preferably from 37 to 49 wt.-%, more preferably from 39 to 47 wt.-%, and more preferably from 41 to 45 wt.-%, based on 100 wt.-% of the composite oxide.
[0098] In the composite oxide, SrAl 12 O 19 The amount of the phase is preferably determined according to the method of Reference Example 1.
[0099] 10. The composite oxide of any one of Embodiments 1 to 9, wherein the composite oxide comprises a Sr(Al2O4) phase.
[0100] 11. A composite oxide as described in Example 10, wherein the composite oxide contains the Sr(Al2O4) phase in an amount ranging from 0.5 to 50 wt.-%, preferably 1 to 40 wt.-%, more preferably 2 to 30 wt.-%, more preferably 3 to 25 wt.-%, 3 to 25 wt.-%, more preferably 4 to 20 wt.-%, more preferably 5 to 18 wt.-%, more preferably 6 to 15 wt.-%, more preferably 7 to 12 wt.-%, and more preferably 8 to 10 wt.-%, based on 100 wt.-% of the composite oxide.
[0101] Wherein the amount of the Sr(Al2O4) phase in the composite oxide is preferably determined according to the method of Reference Example 1.
[0102] 12. The composite oxide of any one of Embodiments 1 to 11, wherein the composite oxide comprises a LaSrAl3O7 phase.
[0103] 13. A composite oxide as described in Example 12, wherein the composite oxide contains the LaSrAl3O7 phase in an amount ranging from 0 to 6 wt.-%, preferably 0.1 to 4 wt.-%, more preferably 0.2 to 3 wt.-%, more preferably 0.4 to 2.5 wt.-%, more preferably 0.6 to 2 wt.-%, 0.6 to 2 wt.-%, more preferably 0.8 to 1.8 wt.-%, more preferably 1.0 to 1.6 wt.-%, and more preferably 1.2 to 1.4 wt.-%, based on 100 wt.-% of the composite oxide.
[0104] The amount of the LaSrAl3O7 phase in the composite oxide is preferably determined according to the method of Reference Example 1.
[0105] 14. The composite oxide of any one of Embodiments 1 to 13, wherein the composite oxide comprises a LaAlO 3 phase.
[0106] 15. The composite oxide as described in Example 14, wherein the composite oxide contains the LaAlO3 phase in an amount ranging from 1 to 35 wt.-%, preferably 3 to 32 wt.-%, more preferably 5 to 30 wt.-%, 10 to 28 wt.-%, more preferably 12 to 25 wt.-%, more preferably 13 to 23 wt.-%, more preferably 15 to 20 wt.-%, and more preferably 17 to 18 wt.-%, based on 100 wt.-% of the composite oxide.
[0107] The amount of the LaAlO3 phase in the composite oxide is preferably determined according to the method of Reference Example 1.
[0108] 16. The composite oxide of any one of Embodiments 1 to 15, wherein the composite oxide comprises a CoAl2O4 phase, preferably a CoAl2O4 spinel phase.
[0109] 17. The composite oxide of embodiment 16, wherein the composite oxide comprises the CoAl2O4 phase in an amount of
[0110] The range is 15.4 to 40 wt.-%, preferably 16.4 to 32 wt.-%, more preferably 17.4 to 28 wt.-%, more preferably 17.9 to 26 wt.-%, more preferably 19 to 24 wt.-%, more preferably 19.5 to 23 wt.-%, more preferably 20 to 22 wt.-%, based on 100 wt.-% of the composite oxide.
[0111] The amount of the CoAl2O4 phase in the composite oxide is preferably determined according to the method of Reference Example 1.
[0112] 18. The composite oxide of any one of Embodiments 1 to 17, wherein the composite oxide comprises a Sr2CoO4 phase.
[0113] 19. The composite oxide of embodiment 18, wherein the composite oxide comprises the Sr2CoO4 phase in an amount ranging from 1 to 20 wt.-%, preferably 3 to 16 wt.-%, 4 to 14 wt.-%, more preferably 5 to 12 wt.-%, more preferably 6 to 10 wt.-%, and more preferably 7 to 8 wt.-%, based on 100 wt.-% of the composite oxide.
[0114] Wherein the amount of the Sr2CoO4 phase in the composite oxide is preferably determined according to the method of Reference Example 1.
[0115] 20. A composite oxide as described in any one of embodiments 1 to 19, wherein the composite oxide comprises 100 wt.-%, 1 wt.-% or less, preferably 0.5 wt.-% or less, more preferably 0.1 wt.-% or less, more preferably 0.05 wt.-% or less, more preferably 0.01 wt.-% or less, more preferably 0.005 wt.-% or less, and more preferably 0.001 wt.-% or less of LaCoAl 11 O 19 phase, wherein the composite oxide preferably does not contain LaCoAl 11 O 19 Mutually,
[0116] Among them, LaCoAl 11 O 19 The amount of the phase is preferably determined according to the method of Reference Example 1.
[0117] 21. A composite oxide as described in any one of embodiments 1 to 20, wherein the composite oxide shows a crystallinity ranging from 30% to 95%, preferably 38% to 87%, more preferably 43% to 82%, more preferably 46% to 79%, more preferably 48% to 77%, more preferably 49% to 76%,
[0118] The crystallinity of the composite oxide is preferably determined according to the method of Reference Example 1.
[0119] 22. The composite oxide of any one of embodiments 1 to 21, wherein 99 to 100 wt-%, preferably 99.5 to 100 wt-%, more preferably 99.9 to 100 wt-% of the composite oxide consists of oxygen, lanthanum, aluminum, strontium, cobalt and optionally hydrogen.
[0120] 23. The composite oxide as described in any one of embodiments 1 to 22, wherein the composite oxide is in the form of a powder or a molded article, preferably in the form of a molded article.
[0121] 24. The composite oxide according to embodiment 23, wherein 99 to 100 wt-%, preferably 99.5 to 100 wt-%, more preferably 99.9 to 100 wt-% of the powder or the molded article consists of the composite oxide.
[0122] 25. The composite oxide of any one of embodiments 1 to 24, wherein the composite oxide is obtained or obtainable according to the method of any one of embodiments 26 to 37.
[0123] 26. A method for producing a composite oxide, preferably a composite oxide according to any one of embodiments 1 to 24, the method comprising
[0124] (i) preparing a mixture of one or more Al sources, one or more Co sources, one or more Sr sources and one or more La sources;
[0125] (ii) adding an acidic aqueous solution to the mixture prepared in (i);
[0126] (iii) homogenizing the mixture obtained in (ii);
[0127] (iv) optionally shaping the mixture obtained in (iii), preferably by extrusion, to obtain a shaped body;
[0128] (v) optionally drying the mixture obtained in (iii) or the shaped body obtained in (iv);
[0129] (vi) optionally pre-calcining the mixture obtained in (iii) or (v), or the shaped body obtained in (iv) or (v);
[0130] (vii) optionally grinding the dried and / or precalcined mixture or shaped body obtained in (v) or (vi);
[0131] (viii) optionally tableting the ground product obtained in (vii);
[0132] (ix) calcining the mixture obtained in (iii), (v), or (vi), or the shaped body obtained in (iv), (v), or (vi), or the ground product obtained in (vii), or the tableted product obtained in (viii).
[0133] 27. A method as described in Example 26, wherein the one or more Al sources are selected from the group consisting of trihydrated alumina, Al2O3·0.5H2O, Al2O3, AlO(OH) - preferably boehmite, sodium aluminate, and a mixture of two or more thereof, preferably selected from the group consisting of gibbsite (α-trihydrated alumina), behemothite (β-trihydrated alumina), nordstrandite (γ-trihydrated alumina), pseudo-amorphous trihydrated alumina, Al2O3·0.5H2O, Al2O3, AlO(OH) - preferably boehmite, sodium aluminate and a mixture of two or more thereof, wherein the one or more alumina sources are more preferably AlO(OH).
[0134] 28. A method as described in Example 26 or 27, wherein the one or more Co sources are selected from the group consisting of cobalt carbonate, cobalt oxalate, cobalt acetate, cobalt tartrate, cobalt formate, cobalt sulfate, cobalt sulfide, cobalt fluoride, cobalt chloride, cobalt bromide, cobalt iodide and a mixture of two or more thereof, wherein the one or more Co sources are preferably cobalt carbonate, more preferably cobalt carbonate, wherein the cobalt carbonate more preferably comprises, more preferably is CoCO3·y H2O, wherein 0≤y≤7, preferably 0≤y≤6.
[0135] 29. The method of any one of embodiments 26 to 28, wherein the one or more La sources are selected from the group consisting of lanthanum carbonate, lanthanum oxalate, lanthanum acetate, lanthanum tartrate, lanthanum formate, lanthanum sulfate, lanthanum sulfide, lanthanum fluoride, lanthanum chloride, lanthanum bromide, lanthanum iodide and a mixture of two or more thereof, wherein the one or more La sources are preferably lanthanum carbonate, wherein the lanthanum carbonate more preferably comprises, more preferably is, La2(CO3)3·x H2O, wherein 0≤x≤10, more preferably 0≤x≤6.
[0136] 30. The method of any one of embodiments 26 to 29, wherein the one or more Sr sources are selected from the group consisting of strontium carbonate, strontium fluoride, strontium chloride, strontium bromide, strontium iodide, strontium sulfate, strontium nitrate, strontium hydroxide, strontium oxide, and a mixture of two or more thereof, wherein the one or more Sr sources are preferably strontium carbonate.
[0137] 31. The method of any one of embodiments 26 to 30, wherein the mixture in (i) is prepared by kneading the one or more Al, Co, Sr and La sources.
[0138] 32. A method as described in any one of Examples 26 to 31, wherein the acidic aqueous solution added in (ii) comprises one or more of formic acid, acetic acid, propionic acid, nitric acid, nitrous acid, citric acid, tartaric acid and oxalic acid, preferably one or more of formic acid and nitric acid, and wherein the acidic aqueous solution added in (ii) more preferably comprises formic acid.
[0139] 33. The process of any one of embodiments 26 to 32, wherein the homogenization in (iii) is achieved by stirring, preferably kneading, the mixture obtained in (ii).
[0140] 34. The method of any one of embodiments 26 to 33, wherein the drying in (v) is carried out at a temperature in the range of 80°C to 150°C, preferably in the range of 95°C to 120°C, more preferably in the range of 100°C to 110°C.
[0141] 35. The method of any one of embodiments 26 to 34, wherein the drying in (v) is performed for a duration in the range of 4 to 18 h, preferably in the range of 6 to 12 h, more preferably in the range of 8 to 10 h.
[0142] 36. The method of any one of embodiments 26 to 35, wherein the pre-calcination in (vi) is carried out at a temperature in the range of 300°C to 600°C, preferably in the range of 350°C to 500°C, more preferably in the range of 400°C to 450°C.
[0143] 37. The method of any one of embodiments 26 to 36, wherein the pre-calcination in (vi) is carried out for a duration in the range of 1 to 8 h, preferably in the range of 3 to 5 h, more preferably in the range of 3.5 to 4.5 h.
[0144] 38. The method of any one of embodiments 26 to 37, wherein the calcination in (vi) is carried out at a temperature in the range of 800°C to 1500°C, preferably in the range of 1000°C to 1400°C, more preferably in the range of 1100°C to 1300°C.
[0145] 39. The method of any one of embodiments 26 to 38, wherein the calcination in (vi) is carried out for a duration in the range of 1 to 8 h, preferably in the range of 3 to 5 h, more preferably in the range of 3.5 to 4.5 h.
[0146] 40. A composite oxide obtainable or obtained according to the method of any one of embodiments 26 to 39.
[0147] 41. A method for producing a catalyst for converting hydrocarbons into synthesis gas, the method comprising
[0148] (1) providing a composite oxide according to any one of Examples 1 to 25 and 40, or preparing a composite oxide according to the method according to any one of Examples 26 to 39;
[0149] (2) Reducing the composite oxide prepared in (1) to obtain a catalyst.
[0150] 42. A method as described in Example 41, wherein the reduction in (2) is carried out in an atmosphere comprising one or more reducing agents, wherein the one or more reducing agents comprise one or more of methane, hydrogen and carbon monoxide, preferably methane and / or hydrogen, wherein methane is more preferably used as the reducing agent in (2).
[0151] 43. A method as described in Example 41 or 42, wherein the reduction in (2) is carried out at a temperature in the range of 500°C to 1,200°C, preferably 600°C to 1,100°C, more preferably 700°C to 1,050°C, more preferably 750°C to 1,000°C, more preferably 800°C to 950°C, and more preferably 850°C to 900°C.
[0152] 44. The method of any one of embodiments 41 to 43, wherein the reduction in (2) is carried out at a pressure in the range of 5 to 40 absolute bar, preferably 10 to 35 absolute bar, more preferably 12 to 30 absolute bar, more preferably 14 to 25 absolute bar, more preferably 16 to 22 absolute bar, and more preferably 18 to 20 absolute bar.
[0153] 45. The method of any one of embodiments 41 to 44, wherein the reduction in (2) is performed for a duration ranging from 0.5 to 24 h, preferably 1 to 18 h, more preferably 3 to 10 h, and more preferably 5 to 7 h.
[0154] 46. A catalyst for converting hydrocarbons into synthesis gas as obtainable or obtained according to the method of any one of embodiments 41 to 45.
[0155] 47. A method for converting hydrocarbons into synthesis gas, the method comprising
[0156] (A) providing the composite oxide according to any one of Embodiments 1 to 25 and 40, or the catalyst according to Embodiment 46;
[0157] (B) preparing a gas stream comprising one or more hydrocarbons and one or more of CO2 and H2O;
[0158] (C) contacting the gas stream prepared in (B) with the composite oxide or the catalyst provided in (A) at a temperature ranging from 700°C to 1,200°C, preferably 750°C to 1,100°C, more preferably 800°C to 1,050°C, more preferably 850°C to 1,000°C, and more preferably 900°C to 950°C.
[0159] 48. The method of embodiment 47, wherein the gas stream prepared in (B) comprises one or more hydrocarbons, CO2, and H2O.
[0160] 49. A method as described in Example 47 or 48, wherein the one or more hydrocarbons are selected from the group consisting of C1-C10 alkanes, preferably C1-C8 alkanes, more preferably C1-C6 alkanes, more preferably C1-C4 alkanes, more preferably C1-C3 alkanes, and more preferably C1-C2 alkanes, wherein the gas stream prepared in (B) more preferably contains one or more of methane, ethane and propane, wherein the gas stream prepared in (B) more preferably contains methane and / or ethane, preferably methane, wherein the one or more hydrocarbons contained in the gas stream prepared in (B) more preferably consist of methane and / or ethane, preferably methane.
[0161] 50. A method as described in any of Examples 47 to 49, wherein the gas stream prepared in (B) contains 20 to 80 vol.-%, preferably 25 to 60 vol.-%, more preferably 30 to 50 vol.-%, more preferably 35 to 45 vol.-%, and more preferably 38 to 42 vol.-% of the one or more hydrocarbons.
[0162] 51. A method as described in any of Examples 47 to 50, wherein the gas stream prepared in (B) contains 20 to 80 vol.-%, preferably 25 to 60 vol.-%, more preferably 30 to 50 vol.-%, more preferably 35 to 45 vol.-%, and more preferably 38 to 42 vol.-% CO2.
[0163] 52. The method of any one of embodiments 47 to 51, wherein the gas stream prepared in (B) comprises 1 to 30 vol.-%, preferably 5 to 25 vol.-%, more preferably 10 to 20 vol.-%, more preferably 12 to 18 vol.-%, and more preferably 14 to 16 vol.-% H2O.
[0164] 53. A method as described in any one of Examples 47 to 52, wherein the gas stream prepared in (B) further comprises one or more inert gases, wherein these inert gases are preferably selected from the group consisting of rare gases, nitrogen and mixtures of two or more thereof, wherein more preferably the gas stream further comprises nitrogen and / or argon, preferably nitrogen.
[0165] 54. A method as described in Example 53, wherein the gas stream prepared in (B) contains 0 to 25 vol.-%, preferably 0.5 to 15 vol.-%, more preferably 1 to 10 vol.-%, more preferably 3 to 8 vol.-%, and more preferably 4 to 6 vol.% of the one or more inert gases.
[0166] 55. The method of any one of embodiments 47 to 54, wherein the contacting in (C) is carried out at a pressure in the range of 5 to 40 absolute bar, preferably 10 to 35 absolute bar, more preferably 12 to 30 absolute bar, more preferably 14 to 25 absolute bar, more preferably 16 to 22 absolute bar, and more preferably 18 to 20 absolute bar.
[0167] 56. The method of any one of embodiments 47 to 55, wherein the contacting in (C) is carried out at a temperature of 500 to 25,000 h. -1 , preferably 1,000 to 15,000h -1 , more preferably 3,000 to 10,000h -1 , more preferably 4,000 to 8,000h -1 , and more preferably 5,000 to 7,000h -1 The gas hourly space velocity is within the range. BRIEF DESCRIPTION OF THE DRAWINGS
[0168] Figure 1 Shown are the results of TPR analysis of samples from Examples 1 to 3 as respectively performed according to Reference Example 2. In the figure, time in minutes is plotted along the abscissa.
[0169] Experimental Section
[0170] The present invention is further illustrated by the following examples, comparative examples and reference examples.
[0171] Reference Example 1: Composition and structure analysis by X-ray diffraction
[0172] The sample was ground using a grinder until it was a fine powder. The grinder used was an IKA tube grinder 100. The grinding program used was 20'000 rpm, 60 s per repeat.
[0173] Afterwards, the sample was transferred to a standard sample holder (material PMMA, manufacturer Bruker AXS) and flattened using a glass plate. The sample was measured in a D8 Advance diffractometer (Bruker AXS) using MoKa1 radiation (fixed slit set to 0.1°) and a linear integral area detector (LynxEye, Bruker AXS) in an angular range of 2°-40° 2θ with a step size of 0.01° 2θ.
[0174] Data analysis was performed using the software TOPAS 6 (TOPAS 6 User Manual, Bruker AXS GmbH, Karlsruhe, Germany, 2017). The simulated phase composition was set to: SrAl 12 O 19, CoAl2O4, LaAlO3, SrAl2O4, Sr2CoO4, LaSrAl3O7. In all phases, the lattice parameters and crystallite sizes were refined and the background was modeled using a third-order polynomial. The sample height was also refined. Intensity corrections for Lorentz and polarization effects were taken into account. Phase quantization was performed using the standard procedure described in Klug, HP and Alexander, LE (1974), X-ray Diffraction Procedures, 2nd edition. New York: John Wiley. The reliability of the refinement was ensured using the additional cost factor of limiting the elemental composition to that measured using the elemental analysis technique (inductively coupled plasma (ICP)).
[0175] Reference Example 2: Temperature Programmed Reduction (TPR) Analysis
[0176] The reduction behavior of the molded article was determined by programmed temperature reduction. A sample of 190 mg of particles with an average particle size between 0.2 and 0.4 mm was used. As feed gas, a flow of 5 volume-% hydrogen in argon was used, wherein the feed rate was set to 50 ml / min. During the measurement, the temperature was increased from room temperature to 950° C. at a heating rate of 5 K / min. The thermal conductivity detector (TCD) signal was recorded relative to the temperature to obtain a TPR curve. The TPR curves of Examples 1-3 are shown in FIG. Figure 1 shown.
[0177] Example 1: Preparation of composite oxides of Co, La, Sr and Al
[0178] 160 g aqueous AlOOH (Disperal; Sasol; containing 77.6 wt.-% Al, calculated as Al2O3), 28.57 g cobalt(II) carbonate hydrate (containing 46 wt.-% Co; Umicore batch 29371A0205 / BASF SE), 40.23 g lanthanum(III) carbonate hydrate (containing 41 wt.-% La; Mongolia Baotuo Steel Rare Earth Int. trade co. ltd) and 17.89 g strontium carbonate (Sigma_Aldrich_Chemie_Germany_GmbH: containing 58.165 wt.-% Sr) were premixed in a kneader for a few minutes. Then, 120 ml of aqueous formic acid (containing 37 wt-% formic acid; based on 98-100 wt-% formic acid, Bernd Kraft GmbH) were added with mixing and a dough-like homogeneous pink mass was formed.
[0179] The kneaded mass was then formed into 3.5 mm ropes. The ropes were dried at 90° C. for 16 h, subsequently calcined at 400° C. for 2 h and then split into particles with an inner diameter of 0.5-1 mm. The split particles were calcined before the catalytic test. For calcination, the molded article was heated to a temperature of 700° C. within 3 hours and the temperature was maintained for 1 hour. The molded article was then further heated to a temperature of 1200° C. and the temperature was maintained for 4 hours. Calcination was carried out in an annealing furnace.
[0180] Structural analysis of the X-ray diffraction data obtained on the calcined sample was performed using the values of the elemental composition of the sample as measured using inductively coupled plasma (ICP) as the elemental analysis technique (see values in Table 1) according to the procedure of Reference Example 1. This analysis provided the following results of the phases in the sample and their relative amounts:
[0181] Phase chemical formula Wt.-% <![CDATA[SrAl 12 THE 19 ]]> 57.7 <![CDATA[CoAl2O4]]> 27.9 <![CDATA[LaAlO3]]> 10.3 <![CDATA[Sr2CoO4]]> 3.0 <![CDATA[SrAl2O4]]> 1.1
[0182] Example 2: Preparation of composite oxides of Co, La, Sr and Al
[0183] 160 g aqueous AlOOH (Disperal; Sasol; containing 77.6 wt.-% Al, calculated as Al2O3), 31.1 g cobalt(II) carbonate hydrate (containing 46 wt.-% Co; Umicore batch 29371A0205 / BASF SE), 80.1 g lanthanum(III) carbonate hydrate (containing 41 wt.-% La; Mongolia Baotuo Steel Rare Earth Int. trade co.ltd) and 35.6 g strontium carbonate (Sigma_Aldrich_Chemie_Germany_GmbH: containing 58.165 wt.-% Sr) were premixed in a kneader for a few minutes. Then, 140 ml of aqueous formic acid (containing 51 wt.-% formic acid; based on 98-100 wt.-% formic acid, Bernd Kraft GmbH) were added with mixing and a dough-like homogeneous pink mass was formed.
[0184] The kneaded mass was then formed into 3.5 mm ropes. The ropes were dried at 90° C. for 16 h, subsequently calcined at 400° C. for 2 h and then split into particles with an inner diameter of 0.5-1 mm. The split particles were calcined before the catalytic test. For calcination, the molded article was heated to a temperature of 700° C. within 3 hours and the temperature was maintained for 1 hour. The molded article was then further heated to a temperature of 1200° C. and the temperature was maintained for 4 hours. Calcination was carried out in an annealing furnace.
[0185] Structural analysis of the X-ray diffraction data obtained on the calcined sample was performed using the values of the elemental composition of the sample as measured using inductively coupled plasma (ICP) as the elemental analysis technique (see values in Table 1) according to the procedure of Reference Example 1. This analysis provided the following results of the phases in the sample and their relative amounts:
[0186]
[0187]
[0188] Example 3: Preparation of composite oxides of Co, Sr, La and Al
[0189] 160 g aqueous AlOOH (Disperal; Sasol; containing 77.6 wt.-% Al, calculated as Al2O3), 31.1 g cobalt(II) carbonate hydrate (containing 46 wt.-% Co; Umicore batch 29371A0205 / BASF SE), 40.03 g lanthanum(III) carbonate hydrate (containing 41 wt.-% La; Mongolia Baotuo Steel Rare Earth Int. trade co. ltd) and 53.39 g strontium carbonate (Sigma_Aldrich_Chemie_Germany_GmbH: containing 58.165 wt.-% Sr) were premixed in a kneader for a few minutes. Then, 140 ml of aqueous formic acid (containing 51 wt.-% formic acid; based on 98-100 wt.-% formic acid, Bernd Kraft GmbH) were added with mixing and a dough-like homogeneous pink mass was formed.
[0190] The kneaded mass was then formed into 3.5 mm ropes. The ropes were dried at 90° C. for 16 h, subsequently calcined at 400° C. for 2 h and then split into particles with an inner diameter of 0.5-1 mm. The split particles were calcined before the catalytic test. For calcination, the molded article was heated to a temperature of 700° C. within 3 hours and the temperature was maintained for 1 hour. The molded article was then further heated to a temperature of 1200° C. and the temperature was maintained for 4 hours. Calcination was carried out in an annealing furnace.
[0191] Structural analysis of the X-ray diffraction data obtained on the calcined sample was performed using the values of the elemental composition of the sample as measured using inductively coupled plasma (ICP) as the elemental analysis technique (see values in Table 1) according to the procedure of Reference Example 1. This analysis provided the following results of the phases in the sample and their relative amounts:
[0192] Phase chemical formula Wt.-% <![CDATA[SrAl 12 THE 19 ]]> 38.1 <![CDATA[SrAl2O4]]> 25.5 <![CDATA[CoAl2O4]]> 18.6 <![CDATA[LaAlO3]]> 12.4 <![CDATA[Sr2CoO4]]> 4.8 <![CDATA[LaSrAl3O7]]> 0.6
[0193] Catalyst characterization
[0194] Elemental analyses of samples from Examples 1 to 3 are shown in Table 1.
[0195] Table 1. Elemental analysis of samples from the Examples (after the second calcination step) as obtained by inductively coupled plasma (ICP).
[0196]
[0197] from Figure 1 The results of the TPR analysis performed on Examples 1 to 3 are shown, and it is noteworthy that as the Co:Sr weight ratio decreases, the temperature peaks appearing in the TPR become lower and lower, which has a positive effect on the activation behavior.
[0198] Thus, it has been unexpectedly found that a Co-containing catalyst formulation containing lanthanum, which further comprises Sr in a Co:Sr weight ratio within a specific range, allows a significantly higher reducibility of the catalyst at low temperatures, as a result of which the activation of the catalyst is significantly improved and can therefore be achieved in a much shorter period of time.
[0199] References
[0200] -WO 2013 / 118078 A1
[0201] -WO 2014 / 135642 A1
[0202] -WO 2015 / 091310 A1
[0203] -US2016 / 0207031 A1
[0204] -US 9566571 B2
[0205] - WO 2014 / 001423 A1
[0206] -WO 2015 / 135968 A1
[0207] - WO 2016 / 062853 A1
[0208] -WO 2020 / 157202 A1
Claims
1. A composite oxide comprising oxygen, lanthanum, aluminum, strontium and cobalt, wherein the weight ratio of cobalt to strontium in the composite oxide is in the range of 0.01:1 to 20:1, calculated as the element.
2. The composite oxide according to claim 1, wherein The composite oxide contains 1 to 15 wt.-% cobalt, calculated as the element.
3. The composite oxide according to claim 1 or 2, wherein The composite oxide contains 1 to 22.0 wt.-% strontium, calculated as the element.
4. The composite oxide according to any one of claims 1 to 3, wherein The composite oxide contains 3.0 to 20.0 wt.-% lanthanum, calculated as the element.
5. The composite oxide according to any one of claims 1 to 4, wherein The composite oxide contains 26.0 to 45 wt.-% aluminum, calculated as the element.
6. The composite oxide according to any one of claims 1 to 5, wherein The composite oxide contains SrAl 12 O 19 Mutually.
7. The composite oxide according to any one of claims 1 to 6, wherein The composite oxide contains a Sr(Al2O4) phase.
8. The composite oxide according to any one of claims 1 to 7, wherein The composite oxide contains a LaSrAl3O7 phase.
9. The composite oxide according to any one of claims 1 to 8, wherein The composite oxide contains a LaAlO3 phase.
10. The composite oxide according to any one of claims 1 to 9, wherein The composite oxide contains a CoAl2O4 phase.
11. The composite oxide according to any one of claims 1 to 10, wherein The composite oxide contains a Sr2CoO4 phase.
12. A method for producing a composite oxide according to any one of claims 1 to 11, the method comprising (i) preparing a mixture of one or more Al sources, one or more Co sources, one or more Sr sources and one or more La sources; (ii) adding an acidic aqueous solution to the mixture prepared in (i); (iii) homogenizing the mixture obtained in (ii); (iv) optionally shaping the mixture obtained in (iii) to obtain a shaped body; (v) optionally drying the mixture obtained in (iii) or the shaped body obtained in (iv); (vi) optionally pre-calcining the mixture obtained in (iii) or (v), or the shaped body obtained in (iv) or (v); (vii) optionally grinding the dried and / or precalcined mixture or shaped body obtained in (v) or (vi); (viii) optionally tableting the ground product obtained in (vii); (ix) calcining the mixture obtained in (iii), (v), or (vi), or the shaped body obtained in (iv), (v), or (vi), or the ground product obtained in (vii), or the tableted product obtained in (viii).
13. A method for producing a catalyst for converting hydrocarbons into synthesis gas, the method comprising (1) providing a composite oxide according to any one of claims 1 to 11, or preparing a composite oxide according to the method of claim 12; (2) Reducing the composite oxide prepared in (1) to obtain a catalyst.
14. A catalyst for converting hydrocarbons into synthesis gas, obtainable or obtained according to the process of claim 13.
15. A method for converting hydrocarbons into synthesis gas, the method comprising (A) providing the composite oxide according to any one of claims 1 to 11, or the catalyst according to claim 14; (B) preparing a gas stream comprising one or more hydrocarbons and one or more of CO2 and H2O; (C) contacting the gas stream prepared in (B) with the composite oxide or the catalyst provided in (A) at a temperature ranging from 700°C to 1,200°C.
Citation Information
Patent Citations
Process for producing a reforming catalyst and the reforming of methane
US20160207031A1
Hexaaluminate-comprising catalyst for the reforming of hydrocarbons and a reforming process
US9566571B2
Hexaaluminate-comprising catalyst for reforming of hydrocarbons and reforming process
WO2013118078A1
High-pressure process for carbon dioxide reforming of hydrocarbons in the presence of iridium-containing active masses
WO2014001423A1
Nickel hexaaluminate-containing catalyst for reforming hydrocarbons in the presence of carbon dioxide
WO2014135642A1